Structure and assembly of double-headed Sendai virus nucleocapsids - Na Zhang (Nature Portfolio, 2021)
The authors present the reconstruction of the Sendai Virus N-RNA complex at atomic resolution, including the helical part and a clam-shaped joint, resolved to 2.9 and 3.9 Å respectively, via cryo-EM. They also demonstrate the presence of an additional, ring like structural motif stabilising Nprotein interactions.